Sodium selenite preserves rBM-MSCs' stemness, differentiation potential, and immunophenotype and protects them against oxidative stress via activation of the Nrf2 signaling pathway - Bahareh Rahimi; Mohammad Panahi; Hajie Lotfi; Mostafa Khalili; Astireh Salehi; Neda Saraygord-Afshari; Effat Alizadeh (BMC, 2023)
Abstract Background The physiological level of reactive oxygen species (ROS) is necessary for many cellular functions. However, during the in-vitro manipulations, cells face a high level of ROS, leading to reduced cell quality. Preventing this abnormal ROS level is a challenging task. Hence, here we evaluated the effect of sodium selenite supplementation on the antioxidant potential, stemness capacity, and differentiation of rat-derived Bone Marrow MSCs (rBM-MSCs) and planned to check our hypothesis on the molecular pathways and networks linked to sodium selenite's antioxidant properties. Methods MTT assay was used to assess the rBM-MSCs cells' viability following sodium selenite supplementation (concentrations of: 0.001, 0.01, 0.1, 1, 10 µM). The expression level of OCT-4, NANOG, and SIRT1 was explored using qPCR. The adipocyte differentiation capacity of MSCs was checked after Sodium Selenite treatment. The DCFH-DA assay was used to determine intracellular ROS levels. Sodium selenite-related expression of HIF-1α, GPX, SOD, TrxR, p-AKT, Nrf2, and p38 markers was determined using western blot. Significant findings were investigated by the String tool to picture the probable molecular network. Results Media supplemented with 0.1 µM sodium selenite helped to preserve rBM-MSCs multipotency and keep their surface markers presentation; this also reduced the ROS level and improved the rBM-MSCs' antioxidant and stemness capacity. We observed enhanced viability and reduced senescence for rBM-MSCs. Moreover, sodium selenite helped in rBM-MSCs cytoprotection by regulating the expression of HIF-1 of AKT, Nrf2, SOD, GPX, and TrxR markers. Conclusions We showed that sodium selenite could help protect MSCs during in-vitro manipulations, probably via the Nrf2 pathway.